2021
DOI: 10.1371/journal.pone.0248135
|View full text |Cite
|
Sign up to set email alerts
|

The perceived impact of multiple sclerosis and self-management: The mediating role of coping strategies

Abstract: Low level of self-management in people with multiple sclerosis (MS) is considered to be a predominant factor that leads to poor rehabilitation efficacy. Studies focusing on the relationship between self-management and psychological variables that can be modified could contribute to expanding the knowledge needed to propose interventional programs aiming at patient activation. This study aimed to analyze whether coping strategies play a mediating role in the association between the perceived impact of MS and le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 44 publications
1
11
0
3
Order By: Relevance
“…In line with other recent findings [19], individuals with disabilities reported moderate levels of stress related to the COVID-19 pandemic, probably due to the high coping strategies that they showed [44,45]. Previous studies showed that disabled athletes have a strong identity as athletes, learning to be focused on their goals [6,46].…”
Section: Discussionsupporting
confidence: 84%
“…In line with other recent findings [19], individuals with disabilities reported moderate levels of stress related to the COVID-19 pandemic, probably due to the high coping strategies that they showed [44,45]. Previous studies showed that disabled athletes have a strong identity as athletes, learning to be focused on their goals [6,46].…”
Section: Discussionsupporting
confidence: 84%
“…Patient adjustment to a new urinary diversion requires important self‐care and disease management skills (Merandy, 2016). Maladaptive coping strategies may hinder patient efforts to emotionally adjust to and develop skills (Wilski et al, 2021) needed for urinary diversion and related challenges (Merandy, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Maladaptive coping strategies may hinder patient efforts to emotionally adjust to and develop skills (Wilski et al, 2021) needed for urinary diversion and related challenges (Merandy, 2016).…”
Section: The Mediation Effects Of Coping On Associations Between Self...mentioning
confidence: 99%
“…Link the patient’s responses to desired behavior changes, pointing out that lifestyle changes move them closer to their wishes. A sense of self-determination via disease control and self-management are valuable, particularly for people with MS because self-management 76 and locus of control 77 are key contributors to MS treatment outcomes. The WBCM Principle 2 shares the motivation and self-determination components with the TPB and SDT.…”
Section: Developing a New Modelmentioning
confidence: 99%